Removal of petroleum hydrocarbons from contaminated groundwater by the combined technique of adsorption onto perlite followed by the O3/H2O2 process - Moussavi, Gholamreza (Environmental technology, 2012)
Groundwater contaminated with petroleum hydrocarbons was treated using a combined system of adsorption onto powdered expanded perlite (PEP) followed by the O3/H2O2 process. The pretreatment investigations indicated a high capacity for PEP to remove petroleum hydrocarbons from the contaminated water. An experimental total petroleum hydrocarbon (TPH) adsorption capacity of 275 mg/g PEP was obtained at the natural pH of water. The experimental data fit best with the Freundlich isotherm model and pseudo-second-order adsorption model. The second phase of the experiment evaluated the performance of the O3/H2O2 process in the removal of residual TPH from pretreated water and compared the results with that of raw water. The O3/H202 process attained a maximum TPH removal rate for the pretreated water after 70 min, when 93% of the residual TPH in the effluent of the adsorption system was removed. Overall, the combination of adsorption onto PEP for 100 min and the subsequent treatment with the O3/H2O2 process for 70min eliminated over 99% of the TPH of highly petroleum-contaminated groundwater, with initial values of 162 mg/L. Therefore, we can conclude that the developed treatment system is an appropriate method of remediation for petroleum-contaminated waters